Social Capital and College Sport - Aaron Walter Clopton (Journal of Intercollegiate Sport, 2011)
Intercollegiate athletics in the United States have been linked with enhancing the sense of community between students on campus (Clopton, 2008). Still, little evidence confirms that maintaining a prominent athletics program contributes to the social capital of students on campus who follow those teams. Consisting of networks of relationships based on trust and norms of reciprocity, social capital is disaggregated into bonding (tightening connections between similar individuals) or bridging (establishing new connections with other members of the campus community) varieties (Putnam, 2000). Results suggest that fan identity detracts from a student’s overall social capital and showed no contribution to one’s bridging social capital. This notion has potential ramification in higher education policy development as the connection between student affairs and athletics is increasingly encouraged (McKindra, 2008).